Knowledge, Attitude and Practice about Safe Drinking Water among High School Teachers of Rawalpindi, Pakistan - Gul Muhammad Shaikh; Asif Maqsood Butt; Muhammad Shafiq (University of Lahore, 2022)
Objective: The objective of the study was to evaluate the knowledge attitude and practice about safe drinking water among high school teachers of Rawalpindi city. Methods: This descriptive study was conducted in Rawalpindi city among high school teachers of some private institutions between September to November in 2021. A total 200 teachers, 151(75%) females and 49 (25%) males participated in the study. Sample selection was done with the help of convenient sampling. Data collection was done with the help of a self-structured questionnaire. Data entry and analysis was done with the help of SPSS version-23. Quantitative variables were presented with the help of mean±SD and qualitative variables were presented with the help of frequency and percentages. Results: Only 67% male and 61% female participants could successfully define perception of safe drinking water. Among male and female participants >80% had knowledge about water borne diseases, less than 50% were able to successfully define water contamination; knowledge about water chlorination was good among participants for both male and female participants as >70% knew about it, perception regarding boiling of water was also high among participants and >80% of male and female participants had perception regarding government role forsafe drinking water and vaccination against water born diseases. In an attempt to name water borne diseases, 23% males & 38% females failed to do so and about 98% males and 99% females had no perception about the nutrients essential in drinking water. Conclusion: Perception about safe drinking water among teachers of high school is unsatisfactory and this is alarming as they are the main source of knowledge for their students and others.